PENGARUH ENTREPRENEURIAL LEADERSHIP DAN ENTREPRENEURIAL INNOVATIVE BEHAVIOR TERHADAP BUSINESS PERFORMANCE MAHASISWA (GENERASI Z) - Beatrix Adelaide Herijanto; Sri Nathasya Br Sitepu (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
The study aims to analyze the impact of entrepreneurial leadership and entrepreneurial innovative behavior on business performance among Generation Z as entrepreneurs at Universitas. In addition, this research also examines the role of entrepreneurial innovative behavior as a mediator in the relationship. The approach used is a quantitative method with a survey technique for data collection. The population involved consists of 235 individuals, with a sample of 193 respondents selected using probability sampling techniques. The data collected through questionnaires were then analyzed using SmartPLS 4.0. The results of the study prove that entrepreneurial leadership has a significant impact on business performance, both directly and through the mediation of entrepreneurial innovative behavior. Innovative behavior also has a proven influence on improving business performance among Generation Z. The implications of this research emphasize the importance of fostering an innovative mindset and strengthening leadership strategies to drive the success of Generation Z's enterprises. Future research is suggested to develop the model by adding more variables and expanding respondents across industries to gain a more comprehensive understanding of the success factors of student entrepreneurs (Generation Z).